Teen pregnancy and parenting: a qualitative study into attitudes and behaviours of teenaged long-term Hispanics in New Mexico. (May 2013) - Osuchowski-Sanchez, Mary Ann; Tigges, Beth; Mendelson, Cindy; Lobo, Marie; Clark, Lauren
Introduction: Teen pregnancy in Hispanic youth is a poorly understood phenomenon with numerous and overlapping sociocultural influences. Hispanics have had the highest teen pregnancy rates in the United States since 1995 and pregnancy rates that have declined much more slowly when compared to every other ethnic group. Literature investigating long-term Hispanic youth of the United States and the factors influencing their decision-making processes and sexual behaviours is limited. Purpose: This study aimed to explore and describe attitudes and behaviours related to teen pregnancy and parenting in Hispanic female teens from long-term families in New Mexico, whose primary language was English and who have experienced pregnancy and motherhood in the 12 months prior to participation. Methods: This was a focused-ethnographic qualitative study conducted in areas of New Mexico with high rates of teen pregnancy and where the population is majority Hispanic with long-term residency. Data were collected in interviews with 10 adolescent mothers and 10 adults, and through participant observation. Data were analysed inductively through immersion and crystallisation. Results: Key findings of the study include chaos/instability characterising the homes of youth, low levels of communication related to reproductive issues, disappointment expressed by families and community in response to teen pregnancy and community goals for the future. Conclusions: The study results will aid in increasing the knowledge base related to long-term Hispanic youth and the many sociocultural factors affecting their sexual decisions and behaviours.